Respuesta :

[tex] {x}^{2} - 5x + 6 = 0[/tex]

[tex](x - 3)(x - 2) = 0[/tex]

[tex]x - 3 = 0 \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: x - 2 = 0[/tex]

[tex] \: \: \: \: \: \: \: x = 0 + 3 \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: x = 0 + 2[/tex]

[tex] \: \: \: \: \: \: \: x = 3 \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: x = 2[/tex]

[tex] \green {\boxed{Answer \: B}}[/tex]

#IfWrongPleaseReport

#StudyTogetherWithMe

#ILoveMath

ACCESS MORE